2020
DOI: 10.1002/ange.201916530
|View full text |Cite
|
Sign up to set email alerts
|

Distal Allylic/Benzylic C−H Functionalization of Silyl Ethers Using Donor/Acceptor Rhodium(II) Carbenes

Abstract: Regio‐ and stereoselective distal allylic/benzylic C−H functionalization of allyl and benzyl silyl ethers was achieved using rhodium(II) carbenes derived from N‐sulfonyltriazoles and aryldiazoacetates as carbene precursors. The bulky rhodium carbenes led to highly site‐selective functionalization of less activated allylic and benzylic C−H bonds even in the presence of electronically preferred C−H bonds located α to oxygen. The dirhodium catalyst Rh2(S‐NTTL)4 is the most effective chiral catalyst for triazole‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Very small quantities were found to enhance the enantioselectivity of rhodium-catalyzed allylic C−H functionalization with 4-aryl-Nsulfonyl triazoles. 33 During recent studies to optimize some specific rhodium-catalyzed cyclopropanation, we discovered that HFIP (10 equiv) desensitizes the reaction to water and N,N′-dimethylaminopyridine (DMAP). 7,34 Given this exciting and unexpected result, we suspected that we could leverage this effect to deactivate a wide range of other nucleophilic poisons and reactive functionality that typically interfere with the cyclopropanation reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very small quantities were found to enhance the enantioselectivity of rhodium-catalyzed allylic C−H functionalization with 4-aryl-Nsulfonyl triazoles. 33 During recent studies to optimize some specific rhodium-catalyzed cyclopropanation, we discovered that HFIP (10 equiv) desensitizes the reaction to water and N,N′-dimethylaminopyridine (DMAP). 7,34 Given this exciting and unexpected result, we suspected that we could leverage this effect to deactivate a wide range of other nucleophilic poisons and reactive functionality that typically interfere with the cyclopropanation reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…41−45 In this study, good reactivity was generally observed with oxygen nucleophiles at low levels of HFIP (Table 3b). Substrates including acetone (32), nitromethane (33), and phenylisocyanate (34) were all tolerated without the use of HFIP. However, more nucleophilic compounds, like N,N′-dimethylformamide (DMF, 39) required 10 equiv HFIP to ensure compatibility.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation